2021
DOI: 10.1200/jco.2021.39.15_suppl.7563
|View full text |Cite
|
Sign up to set email alerts
|

A novel index using inflammatory markers improves the diagnosis of hemophagocytic lymphohistiocytosis in patients with hematologic malignancies.

Abstract: 7563 Background: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening inflammatory syndrome that may accompany hematologic malignancies (HM). The diagnosis of HLH in patients with HM (HM-HLH) is confounded by a number of factors: the most commonly used HLH-2004 diagnostic criteria are derived from studies in infants while the Hscore used in adults is not specific for HMs; moreover, most parameters in these scoring systems may reflect features of the underlying HM rather than HLH associated inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study analyzed DTI and MRI parameters in acute and chronic phase with clinical scores of 3 months after injury and found that (1) DTI and MRI parameters can predict recovery and guide treatment in coma TBI patients compared with normal controls [ 20 ] (2) DTI and MRI can indicate the prognosis of coma patients with TBI [ 21 ] (3) parameter recovery in ARAS is slower than that in the thalamus, and (4) ARAS parameters can better predict the prognosis of coma patients [ 22 ]. DTI analysis of patients with TBI coma showed that in the acute phase, the parameters in ARAS and thalamus were significantly different from those of normal controls, but the recovery of the parameters within ARAS was slower than that within the thalamus, and the parameters gradually improved with the stability of the condition during the chronic period.…”
Section: Results and Analysismentioning
confidence: 99%
“…This study analyzed DTI and MRI parameters in acute and chronic phase with clinical scores of 3 months after injury and found that (1) DTI and MRI parameters can predict recovery and guide treatment in coma TBI patients compared with normal controls [ 20 ] (2) DTI and MRI can indicate the prognosis of coma patients with TBI [ 21 ] (3) parameter recovery in ARAS is slower than that in the thalamus, and (4) ARAS parameters can better predict the prognosis of coma patients [ 22 ]. DTI analysis of patients with TBI coma showed that in the acute phase, the parameters in ARAS and thalamus were significantly different from those of normal controls, but the recovery of the parameters within ARAS was slower than that within the thalamus, and the parameters gradually improved with the stability of the condition during the chronic period.…”
Section: Results and Analysismentioning
confidence: 99%